Application of group-theoretical methods to point explosion problem in incompressible liquid - Yuryk, Ivan (My University, 2015)
Group-theoretical methods are applied to find particular solutions to differential systems in hydrodynamics. Obtained solutions that satisfy the Rankine-Hugoniot conditions is used to describe a point explosion in incompressible liquid.
Keywords: кафедра вищої математики імені проф. Можара В. І.; incompressible liquid; point explosion; group-theoretical methods problem; нестислива рідина; точковий вибух; теоретико-групові методи